Calreticulin exploits TGF‐β for extracellular matrix induction engineering a tissue regenerative process. Issue 12 (5th October 2020) - Pandya, Unnati M.; Manzanares, Miguel A.; Tellechea, Ana; Egbuta, Chinaza; Daubriac, Julien; Jimenez‐Jaramillo, Couger; Samra, Fares; Fredston‐Hermann, Alexa; Saadipour, Khalil; Gold, Leslie I.
Abstract: Topical application of extracellular calreticulin (eCRT), an ER chaperone protein, in animal models enhances wound healing and induces tissue regeneration evidenced by epidermal appendage neogenesis and lack of scarring. In addition to chemoattraction of cells critical to the wound healing process, eCRT induces abundant neo‐dermal extracellular matrix (ECM) formation by 3 days post‐wounding. The purpose of this study was to determine the mechanisms involved in eCRT induction of ECM. In vitro, eCRT strongly induces collagen I, fibronectin, elastin, α‐smooth muscle actin in human adult dermal (HDFs) and neonatal fibroblasts (HFFs) mainly via TGF‐β canonical signaling and Smad2/3 activation; RAP, an inhibitor of LRP1 blocked eCRT ECM induction. Conversely, eCRT induction of α5 and β1 integrins was not mediated by TGF‐β signaling nor inhibited by RAP. Whereas eCRT strongly induces ECM and integrin α5 proteins in K41 wild‐type mouse embryo fibroblasts (MEFs), CRT null MEFs were unresponsive. The data show that eCRT induces the synthesis and release of TGF‐β3 first via LRP1 or other receptor signaling and later induces ECM proteins via LRP1 signaling subsequently initiating TGF‐β receptor signaling for intracellular CRT (iCRT)‐dependent induction of TGF‐β1 and ECM proteins. In addition, TGF‐β1 induces 2‐3‐fold higher level of ECM proteins than eCRT. Whereas eCRT and iCRT converge for ECM induction, we propose that eCRT attenuates TGF‐β‐mediated fibrosis/scarring to achieve tissue regeneration.